n 2 { n }^{ 2 } and 2 n { 2 }^{ n }

How many positive integers n n such that 4 n + 2 n + 1 n 2 + n + 1 \dfrac { { 4 }^{ n }+{ 2 }^{ n }+1 }{ { n }^{ 2 }+{ n }+1 } is a positive integer?

If you think that there are infinitely many such " n n "s, type -777487.


The answer is -777487.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Patrick Corn
Jul 31, 2019

Lemma: n 2 + n + 1 n^2+n+1 divides n 2 a + n a + 1 n^{2a} + n^a + 1 as long as a a is not divisible by 3. 3.

Proof: Since x 2 + x + 1 x^2+x+1 is the minimal polynomial of ω , \omega, a primitive third root of unity , it is enough to note that ω 2 a + ω a + 1 = 0. \omega^{2a} + \omega^a + 1 = 0. \Box

Now, to solve the problem, let k k be a nonnegative integer. Let m = 2 k . m = 2^k. Let n = 2 m . n = 2^m. Let a = 2 m k , a = 2^{m-k}, so that m a = n . ma=n. Then n 2 a + n a + 1 = 4 m a + 2 m a + 1 = 4 n + 2 n + 1. n^{2a} + n^a + 1 = 4^{ma} + 2^{ma} + 1 = 4^n + 2^n + 1.

By the lemma, then, since a a is not divisible by 3 , 3, 4 n + 2 n + 1 n 2 + n + 1 \frac{4^n+2^n+1}{n^2+n+1} is an integer. There are infinitely many k , k, hence infinitely many n . n.

Mark Hennings
Aug 1, 2019

A slightly different approach to Patrick's...

For any m N { 0 } m \in \mathbb{N} \cup \{0\} , define k = 2 2 m m 1 k = 2^{2^m-m}-1 . Then k + 1 k+1 is a power of 2 2 , so is coprime to 3 3 . Thus the map u 3 u u \mapsto 3u from Z k + 1 \mathbb{Z}_{k+1} to itself is bijective. For any positive integer n n , u = 0 k n 3 u u = 0 k n f ( u ) u = 0 k n u ( m o d n k + 1 1 ) \sum_{u=0}^k n^{3u} \; \equiv \; \sum_{u=0}^k n^{f(u)} \; \equiv \; \sum_{u=0}^k n^u \hspace{1cm} \pmod{n^{k+1}-1} so we deduce that u = 0 k n 3 u u = 0 k n u 0 ( m o d j = 0 k n u ) \sum_{u=0}^k n^{3u} \equiv \sum_{u=0}^kn^ u \; \equiv \; 0 \hspace{1cm} \pmod{\sum_{j=0}^k n^u} which implies that u = 0 k n 3 u u = 0 k n u \frac{\displaystyle\sum_{u=0}^k n^{3u} }{\displaystyle\sum_{u=0}^k n^u} is an integer. Now note that ( 1 + n + n 2 ) ( u = 0 k n 3 u ) = u = 0 3 k + 2 n u = ( 1 + n k + 1 + n 2 k + 2 ) ( u = 0 k n u ) (1 + n + n^2)\left(\sum_{u=0}^k n^{3u}\right) \; = \; \sum_{u=0}^{3k+2}n^u \; =\; \big(1 + n^{k+1} + n^{2k+2}\big) \left(\sum_{u=0}^k n^u\right) and hence we see that n 2 k + 2 + n k + 1 + 1 n 2 + n + 1 = u = 0 k n 3 u u = 0 k n u \frac{n^{2k+2} + n^{k+1} + 1}{n^2 + n + 1} \;= \; \frac{\displaystyle\sum_{u=0}^k n^{3u} }{\displaystyle\sum_{u=0}^k n^u} is an integer. If we now put n = 2 2 m n = 2^{2^m} then n k + 1 = 2 ( k + 1 ) 2 m = 2 2 2 m = 2 n n^{k+1} \; = \; 2^{(k+1)2^m} \; = \; 2^{2^{2^m}} \; = \; 2^n and hence we deduce that 4 n + 2 n + 1 n 2 + n + 1 \frac{4^n + 2^n + 1}{n^2 + n + 1} is an integer whenever n = 2 2 m n = 2^{2^m} for any m N { 0 } m \in \mathbb{N}\cup\{0\} . Thus the answer is 777487 \boxed{-777487} .

K T
Aug 2, 2019

Observe that n=2 and n=4 and n=16 are solutions. Maybe every n = 2 2 k n=2^{2^k} is?

Without a rigorous proof, I could see a pattern in the polynomial divisions below that made me quite confident that it would always come out for such n.

k n 4 n + 2 n + 1 4^n+2^n+1 polynomial division quotient ( 4 n + 2 n + 1 ) / ( n 2 + n + 1 ) (4^n+2^n+1)/(n^2+n+1)
0 2 n 4 + n 2 + n 0 n^4+n^2+n^0 n 2 n 1 + n 0 n^2-n^1+n^0
1 4 n 4 + n 2 + n 0 n^4+n^2+n^0 n 2 n 1 + n 0 n^2-n^1+n^0
2 16 n 8 + n 4 + n 0 n^8+n^4+n^0 n 6 n 5 + n 3 n 1 + n 0 n^{6}-n^{5}+n^{3}-n^1+n^0
3 256 n 64 + n 32 + n 0 n^{64}+n^{32}+n^0 n 62 n 61 + n 59 n 58 . . . + n 32 n 31 + n 30 n 28 + n 27 n 26 . . . n 4 + n 3 n + 1 n^{62}-n^{61}+n^{59}-n^{58}...+n^{32}-n^{31}+n^{30}-n^{28}+n^{27}-n^{26}...-n^4+n^3-n+1

Observe that

  • n 3 k / ( n 2 + n + 1 ) = t = k n 3 t 2 n 3 t 3 n^{3k}/(n^2+n+1) = \sum_{t=-\infty}^{k}n^{3t-2}-n^{3t-3}
  • n 3 k + 1 / ( n 2 + n + 1 ) = t = k n 3 t 1 n 3 t 2 n^{3k+1}/(n^2+n+1) = \sum_{t=-\infty}^{k}n^{3t-1}-n^{3t-2}
  • n 3 k + 2 / ( n 2 + n + 1 ) = t = k n 3 t n 3 t 1 n^{3k+2}/(n^2+n+1) = \sum_{t=-\infty}^{k}n^{3t}-n^{3t-1}

Observe that the three powers of n in each row (e.g. 64 , 32 64, 32 and 0 0 ) have different remainders (mod 3), so that the infinite tails of their power series cancel out, and the division becomes finite.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...